An investigation on people’s participation in village assembly: A case of Biharamulo District council, Tanzania - Ndikwiki, Edosi (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Public Administration (MPA) of Mzumbe University